EFFICACY OF IMMUNONUTRITION CONTAINING OMEGA-3 FATTY ACIDS TO REDUCE MORTALITY IN ACUTE RESPIRATORY DISTRESS SYNDROME: AN EVIDENCED-BASED CASE REPORT - Nita; Wiji Lestari (IJCNP : INDONESIAN JOURNAL OF CLINICAL NUTRITION PHYSICIAN, 2022)
Background: Acute respiratory distress syndrome (ARDS) remains one among the most reasons for ICU admission. It is related to high rates of mortality despite many recent advances in overall support. A relative increase in oxidative stress in patients with ARDS results in increased alveolar injury. Immunonutrion containing omega 3 fatty acids is one among the strategies that currently receiving attention within the management of ARDS since they are known to have anti-inflammatory effects, but the results are still inconsistent. Objective: This study aimed to find out the efficacy of immunonutrition containing omega 3 fatty acids in reducing mortality in patients with ARDS. Methodology: Electronic literature researches were performed in PubMed, Cochrane, and Scopus. MeSH term and title/abstracts were screened based on inclusion and exclusion criteria before relevant journals were reviewed. Results: Two articles were selected based on the eligibility criteria and relevance to the clinical questions. The study of Langlois P. et al. found significantly reduced mortality in patients receiving continuous enteral infusion route of immunonutrition containing omega 3 fatty acids. While Dushianthan A. et al. found little or no mortality benefit with the administration of immunonutrition containing omega 3 fatty acids. Conclusions: There is little or no mortality reduction within the administration of immunonutrition containing omega 3 fatty acids. Keywords: acute respiratory distress syndrome, ARDS, immunonutrition, omega 3 fatty acids, mortality.